A Critical Evaluation of Qualitative Reports and Their Contributions to Educational Research - Abrar, Mukhlash (PAROLE: Journal of Linguistics and Education, 2017)
This purpose of this article was to critically assert the contribution of qualitative research in education. The article offers a theoretical exploration of qualitative (qualitative historical background, features, methods and qualitative strengths and weaknesses) and a structural critical analysis on qualitative studies (study purpose, literature review, study design, method, results and discussion, and conclusion). Two qualitative education research paper were selected and analysed with a view to arguing that qualitative research gives more contributions than others. The results of the analysis indicated that qualitative research positively contributes to education research in many ways, including the possibility of direct interaction in gathering the data, and providing in-depth and critical interpretation of meanings